KAJIAN DAKTILITAS DAN KEKAKUAN PERKUATAN BALOK T DENGAN KABEL BAJA PADA MOMEN NEGATIF - Dimas Langga Chandra Galuh; Hadi Pangestu Rihardjo (Universitas Sarjanawiyata Tamansiswa, 2016)
Strengthening is a solution to improve supporting power of the boned concrete structure and strengthening the endurance of building. This research aims to find out the stiffness, ductility and cracking pattern of the negative moment area of beam. This research used three experimental beams, they are 1 control beam (BK), 1 strengthening beam 4Ã˜10 mm of steel cable on pulling area (BP1) and 1 strengthening beam using 4Ã˜10 mm of steel cable on pulling area and 2P8 mm on the pressing area (BP2) using mortar as the concrete blanket. The experimental object was in form of boned concrete beam T, with 2400 of length (l), 250 mm of height (h), 150 mm of width (bw), 400 mm of width of flens (t), 75 mm of height of flens (t). The steel cable and the diameter of boned steel used for strengthening process is 10 mm and 8 mm of plain type. The beam would be tested on the basis of flexibility by using static loading and simple support. The measurement of load, tension, and flexibility was done during the experiment (testing). Based on the results of experiment, it is shown that the maximum loads on the testing objects of BK, BP1, and BP2 respectively are 88.5 kN and 259 kN. The ratio of stiffness comparison of initial stiffness BP1 and BP2 to BK was 0.33 and 0.48. The ratio of ductility comparison of BP1 and BP2 to BK was 0,33 and 0.48. The collapsing pattern of each strengthening beam was debonding, but the steel cable on the strengthening beam still contributed the pulling tension, so the existing load kept on increasing until reaching maximum load.